A methodological approach for environmental characterization of ports. Issue 1 (2nd January 2017) - Papaefthimiou, S.; Sitzimis, I.; Andriosopoulos, K.
ABSTRACT: This paper introduces a methodology for the characterization of ports, employing specifically defined eco-efficiency indicators and combining typically available data (handled cargo, containers and passengers) with ship exhaust pollutants values (mainly NOx, SOx and PM) and anticipated external costs (ECs) due to emitted air pollutants to provide a collective overview of all port-related economic and environmental activities. The results from an applied case study allow a comparative evaluation of 16 selected ports based on 17 different evaluation criteria and denote that the employment of such an overall approach can allow port authorities to improve managerial aspects, potentially lower operational costs and promote reduced environmental effects.